Assessment of the Relationship Between Student-Teacher Interactions and Professional Development among Nursing Students in Karachi, Pakistan: Relationship Between Student-Teacher Interactions and Professional Development - Razzaque, Muhmooda Abdul; Haroon, Rukhsana Muhammad; Hafeez, Rubina; Ahmed, Tanseer (Pakistan Journal of Health Sciences, 2025)
Student-teacher interactions (STIs) and professional development (PD) are a crucial part of nursing education. Both contribute to enhancing self-efficacy among nursing students by fostering knowledge, skills, and professional identity. Objectives: To assess the relationship between student-teacher interactions and professional development among nursing students in Karachi, Pakistan. Methods: A cross-sectional analytical study was conducted between November 2024 and January 2025 at two nursing institutions: Dow Institute of Nursing and Midwifery and the College of Nursing, Dr Ruth Pfau Civil Hospital, Karachi. A purposive sample of 235 Bachelor of Science in Nursing (BSN) students was included from the 2nd to 4th years of nursing students. After getting ethical approval and consent from the participants. Data were gathered using a structured, self-developed questionnaire. Data were analyzed using SPSS version 26.0. Results: Out of 235, the mean age (25.9 ± 0.891) of the participants, and a majority were female (n=157, 66.8%), and were studying in their 4th year (n=122, 51.9%). A bulk of participants were not aware of the hidden curriculum. They found a significant positive correlation between STIs and PD (Spearman’s ρ = 0.789, p<0.01) among respondents. Conclusions: This study found a strong relationship between student–teacher interactions and professional development among nursing students in Karachi, Pakistan. It is recommended to conduct longitudinal and qualitative studies to gain deeper insights into student–teacher interactions and their relationship with professional development among nursing students.